Work-Life Balance, Organizational Commitment, and Job Satisfaction to Improve Millennial Generation Employee Performance at PT Aneka Coffee Industry - Meganita Chintya; Gustaf Naufan Febrianto; Angga Dutahatmaja (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2026)
This study aims to analyze the influence of work-life balance, organizational commitment, and job satisfaction on employee performance of millennial generation at PT Aneka Coffee Industry. This research uses quantitative method with multiple linear regression analysis. The population consists of 120 millennial employees at staff level in Production and HRD & GA departments, with 95 respondents selected using purposive sampling technique. Data collection was conducted through questionnaires using Likert scale. The results show that work-life balance has a positive and significant effect on employee performance (β=0.258, p=0.008), organizational commitment has a positive and significant effect on employee performance (β=0.162, p=0.034), and job satisfaction has a positive and significant effect on employee performance with the most dominant influence (β=0.525, p<0.001). Simultaneously, the three variables significantly influence employee performance with R² value of 0.781 (78.1%). This study provides practical implications for companies to develop HR policies that support work-life balance, strengthen organizational commitment, and increase employee job satisfaction to optimize millennial employee performance.